Effect of using some spices to control the adults of red flour beetle Tribolium castanaeum (Herbest) (Coleoptera: Tenebrionidae) - Fouad A.Abdullha (Tikrit Journal of Pure Science, 2023)
The study aims to investigate insecticidal and the repellency effects of three powders Capsicum annuum , Piper nigrum and Zingiber officinale against the red flour beetle T. castaneum. Mortality percentages of  the following concentrations 0.5, 1, 2, 3gram (w/w) of powders which were mixed with crushed wheat grains were calculated after 96 hours, percentage of the repellency effect of the same concentrations were calculated after 48 hours. The results showed highly significant differences among concentration of powder. Also results showed significans effect of Piper nigrum powder at concentration 3g , for repellency effect with value 9.590% while the value for C. annuum and Z. officinale powders at the same concentration were 8.665% and 6.000% respectively well as the insecticidal effect for concentration 3g were 6.312%, 7.360%, 4.000% C. annuum, P. nigrum and Z. officinale powders respectively .